EXPLORING STUDENTS’ WRITING OF NEWS REPORT AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Roslianti Laode; Anwar Ismail; Muamar Abd Halil (Cakrawala Bahasa, 2020)
The aim of this research is to know students’ competence in writing news report at the sixth semester of English Education Study Program at Khairun University. The researcher focuses on students’ writing news report text concering generic structure of the news that included headline, newsworthy of event, background of event and source. The researcher applied qualitative research method, this research involved 15 respondents of sixth Semester of English Language Education Study Program at Khairun University. The researcher used written test the data obtained were analyzed by using content analysis. The result of the data analysis shows that students’ writing in headline of the news 60% (nine students) acquired low competence, 26.6% (four students) acquired middle competence and 13.3% (two students) acquired high competence. Students’ writing in newsworthy of event 53.3% (eight students) acquired low competence, 40% (six students) acquired middle competence and 6.66% (one student) acquired high competence. students’ writing in background of event 53.3% (eight students) acquired low competence, 33.3% (five students) acquired middle competence and 13.3% (two students) acquired high competence. Students’ writing in source there are 6.66% (one student) acquired low competence, 86.6% (13 students) acquired middle competence and 6.66% (one student) acquired high competence. This suggests that, 1) More than 80% students have middle competence in writing source; 2) as accurate, 50-60% students have low competence in writing headline, newsworthy of event and background of event; 3) however, 26-53% students have middle competence in writing newsworthy of event, background of event and headline; 4) moreover, 6-13% students have high competence in writing headline, background of event and source.